Cost–benefit comparison of two proposed overseas programs for reducing chronic Hepatitis B infection among refugees: Is screening essential?. Issue 11 (10th March 2015) - Jazwa, Amelia; Coleman, Margaret S.; Gazmararian, Julie; Wingate, La'Marcus T.; Maskery, Brian; Mitchell, Tarissa; Weinberg, Michelle
Abstract Background Refugees are at an increased risk of chronic Hepatitis B virus (HBV) infection because many of their countries of origin, as well as host countries, have intermediate-to-high prevalence rates. Refugees arriving to the US are also at risk of serious sequelae from chronic HBV infection because they are not routinely screened for the virus overseas or in domestic post-arrival exams, and may live in the US for years without awareness of their infection status. Methods A cohort of 26, 548 refugees who arrived in Minnesota and Georgia during 2005–2010 was evaluated to determine the prevalence of chronic HBV infection. This prevalence information was then used in a cost–benefit analysis comparing two variations of a proposed overseas program to prevent or ameliorate the effects of HBV infection, titled 'Screen, then vaccinate or initiate management' (SVIM) and 'Vaccinate only' (VO). The analyses were performed in 2013. All values were converted to US 2012 dollars. Results The estimated six year period-prevalence of chronic HBV infection was 6.8% in the overall refugee population arriving to Minnesota and Georgia and 7.1% in those ≥6 years of age. The SVIM program variation was more cost beneficial than VO. While the up-front costs of SVIM were higher than VO ($154, 084 vs. $73, 758; n = 58, 538 refugees), the SVIM proposal displayed a positive net benefit, ranging from $24 million to $130 million after only 5 years since program initiation, depending on domestic post-arrival screening rates in the VO proposal. Conclusions Chronic HBV infection remains an important health problem in refugees resettling to the United States. An overseas screening policy for chronic HBV infection is more cost–beneficial than a 'Vaccination only' policy. The major benefit drivers for the screening policy are earlier medical management of chronic HBV infection and averted lost societal contributions from premature death.